2020
DOI: 10.1159/000506150
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of TRIM Family Proteins in Cardiovascular Disease

Abstract: Ubiquitination is one of the basic mechanisms of cell protein homeostasis and degradation and is accomplished by 3 enzymes, E1, E2, and E3. Tripartite motif-containing proteins (TRIMs) constitute the largest subfamily of RING E3 ligases, with > 70 current members in humans and mice. These members are involved in multiple biological processes, including growth, differentiation, and apoptosis as well as disease and tumorigenesis. Accumulating evidence has shown that many TRIM proteins are associated with various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 104 publications
0
9
0
Order By: Relevance
“…Finally, it is worth noting that various TRIM proteins have been implicated in metabolic disorders, ranging from obesity (i.e., TRIM23, TRIM25, TRIM28, and TRIM67) [ 51 , 52 ] to diabetes (i.e., TRIM7, TRIM27, TRIM32, and TRIM72), [ 53 ] as well as cardiovascular diseases [ 54 ]. The muscle-specific TRIM called Mitsugumin 53 (MG53 or TRIM72) is leading research attention in this field, and it has been shown to negatively regulate myogenesis and promote diabetic as well as cardiovascular complications.…”
Section: Trim Proteins: An Overview Of Structure and Functionmentioning
confidence: 99%
“…Finally, it is worth noting that various TRIM proteins have been implicated in metabolic disorders, ranging from obesity (i.e., TRIM23, TRIM25, TRIM28, and TRIM67) [ 51 , 52 ] to diabetes (i.e., TRIM7, TRIM27, TRIM32, and TRIM72), [ 53 ] as well as cardiovascular diseases [ 54 ]. The muscle-specific TRIM called Mitsugumin 53 (MG53 or TRIM72) is leading research attention in this field, and it has been shown to negatively regulate myogenesis and promote diabetic as well as cardiovascular complications.…”
Section: Trim Proteins: An Overview Of Structure and Functionmentioning
confidence: 99%
“…Functional studies have demonstrated that different TRIMs, such as TRIM8, TRIM10, TRIM21, TRIM24, TRIM28, TRIM32, TRIM37, TRIM45, TRIM50, TRIM67, TRIM72 and TRIM76, have distinct effects on cardiac function and cardiac pathology, and are involved in cardiomyocyte apoptosis, ischemia–reperfusion injury, myocardial dysplasia and cardiomyopathy ( Yang et al, 2020 ; Chen et al, 2017 , 2012 ; Heliste et al, 2020 ; Borlepawar et al, 2019 ; Gupta et al, 2018 ; Brigant et al, 2018 ; Zhang et al, 2020 ; Rabinovich-Nikitin and Kirshenbaum, 2019 ; Zhang et al, 2021 ). Given the complexity of cardiac physiology and pathology, few TRIMs have been shown to have effects on the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%
“…They play crucial roles in various physiological and pathological processes including DNA repair, apoptosis, autophagy, innate immunity, cell proliferation and development, and carcinogenesis [7] , [8] , [9] . Their dysregulation causes various diseases including cancer, infectious inflammatory, cardiovascular diseases, and neuropsychiatric disorders [10] , [11] , [12] . TRIM proteins usually consist of a conserved N -terminal tripartite motif: RING domain, B box (B box1 and/or B box 2), and coiled-coil domain, and a diverse C-terminal domain that determines substrate specificity.…”
Section: Introductionmentioning
confidence: 99%